MULTIPLE CHRONIC KIDNEY DISEASES (Journal of Universal Science Research, 2023)
Kidneys perform a very important function in the body. One liter of blood passes through them in a minute, it is constantly cleaned of toxins and harmful substances. It produces biologically active substances, in particular, renin, which regulates blood pressure, and erythropoietin, which regulates the rate of formation of erythrocytes. It helps to control the water balance and the concentration of minerals such as sodium, potassium, and phosphorus in the blood. This article provides information about common kidney diseases and their treatment methods.